Analysis of Factors Influencing Women Entrepreneurship - Wahyuddin, Masriani; Pratiwi, Yayu Chandra (Jurnal Economic Resource, 2025)
The role of women in the business world needs to be considered, especially in the field of entrepreneurship. Women entrepreneurs are part of the Indonesian Women with Disabilities Association (HWDI). HWDI is an organization for women, where most of the board and members are women with various types of disabilities (physical, sensory, mental, and intellectual). Women with disabilities also need to be encouraged to be empowered and equal to other women, both in terms of working and creating new job opportunities. This research aims to identify the factors that influence women in entrepreneurship, both internal and external factors, in HWDI Bantaeng Regency. This research uses a quantitative method. The data collection technique used a questionnaire and was analyzed using SPSS version 27. The research results show that only a few internal factors (interest, self-empowerment, motivation, independence, emotional state, education) and external factors (support from husband/family, funding sources, family environment, social environment, and opportunities) influence women entrepreneurs. The variables that were found to have an influence are interest, motivation, independence, emotional state, family support, funding sources, and family environment.